Chlorophyll a Concentration of Phytoplankton during the Cruise of the 47th Japanese Antarctic Research Expedition in 2005-2006 - Honda, Masaki; Ichinomiya, Mutsuo; Saito, Kenji; Otsuki, Akihisa S.; Hirawake, Toru; Fukuchi, Mitsuo (National Institute of Polar Research, 2007)
P(論文) departmental bulletin paper